The Use of the Ambulatory Arterial Stiffness Index in Patients Suspected of Secondary Hypertension - Verbakel, Joshua R. A.; Adiyaman, Ahmet; Kraayvanger, Nicole; Dechering, Dirk G.; Postma, Cornelis T. (Frontiers in Cardiovascular Medicine, 2016)
The Ambulatory Arterial Stiffness Index (AASI) is a marker of arterial stiffness and is derived from ambulatory 24-hour blood pressure registration. We studied whether the AASI could be used as a predictive factor for the presence of Renal Artery Stenosis (RAS) in patients with a suspicion of secondary hypertension and as such as a diagnostic tool for RAS. We included 169 patients with difficult-to-treat hypertension. They all underwent 24-hour ABPM registration, imaging of the renal arteries and cardiovascular risk measurement, including smoking, history, biometrics, blood pressure, renal function, lipids and glucose metabolism. Performing univariate and multivariate analyses, we investigated if AASI and the other cardiovascular risk factors were related to the presence of RAS. Of the 169 patients (49% women), 31% had RAS. The mean AASI was 0.44 (0.16). The presence of RAS showed no significant correlation with AASI (r =0.14, P=0.06). Age (r =0.19, P =0.01), hypercholesterolemia (r=0.26, p=0.001), history of CVD (r =0.22, P =0.004) and creatinine clearance (r=-0.34, P<0.001) all demonstrated a correlation with RAS. Although AASI is higher in patients with RAS, AASI does not independently predict the presence of RAS in hypertensive subjects.